Molecular Design and Control Over the Morphology of Self‐Assembled Films on Ionic Substrates. Issue 9 (25th November 2014) - Amrous, Ania; Bocquet, Franck; Nony, Laurent; Para, Franck; Loppacher, Christian; Lamare, Simon; Palmino, Frank; Cherioux, Fréderic; Gao, David Z.; Canova, Filippo Federici; Watkins, Matthew B.; Shluger, Alexander L.
<x xml:space="preserve">Abstract</x> Achieving control over formation of molecular films on insulating substrates is important for designing novel 2D functional materials and devices. To study the main factors governing successful control, organic molecules with interchangeable polar functional groups, a variable length aromatic body, and flexible hydrocarbon chains are designed, synthesized and then deposited on the (001) surfaces of bulk sodium chloride, potassium chloride, and rubidium chloride. The deposited structures are imaged using noncontact atomic force microscopy and modeled using density functional theory. The results show that it is possible to form large‐scale, highly ordered, 2D, porous molecular domains (>104 pores), which are stable at room temperature, and to control the size of the 2D pores. Alternatively, it is possible to form line structures or droplets (through molecular dewetting) by altering the molecular structure or changing the substrate lattice constant. Theoretical calculations explain the balance of the molecule–molecule and molecule–surface interactions and the structure and thermodynamic stability of the grown films.